Desmopressin as an Alternative Solution for Urinary Leakage After Ureterocaliceal Surgeries - Razzaghi, Mohammad Reza; Rezaei, Alireza; Javanmard, Babak; Lotfi, Behzad (Urology Journal, 2009)
Introduction: Persistent urine leakage is common following iatrogenic urinary collecting system injuries. Management of a urine leak usually includes manipulations such as catheter drainage, ureteral stenting, and percutaneous nephrostomy placement. The aim of this study was investigation the potential beneficial effect of desmopressin in reduction of urinary leakage duration. Materials and Methods: Fifteen patients with incisional urinary leakage were enrolled in this study. They had undergone pyeloplasty (n = 9), pyelolithotomy (n = 4), and ureterocaliceal anastomosis (n = 1). All of them had ureteral stenting or nephrostomy catheters, and urinary leakage had lasted for at least 15 days. Seven patients received desmopressin spray, 1 puff, twice a day, from the 16th days of urinary leakage, and 8 patients (control group) did not receive any medical treatment. The duration of urinary leakage was compared between the two groups. Results: The patients were 5 women and 10 men with the median age of 37 years (range, 26 to 58 years). None of the patients had urinary obstruction. There were no significant differences in age and sex distribution between the two groups. The mean urinary leakage duration was 28.7 Â± 7.2 days in the patients of desmopressin group and 47.7 Â± 8.8 days in those of the control group (P = .04). Conclusion: Our study showed that desmopressin can reduce the duration of incisional urinary leakage. We conclude that patients with prolonged urinary leakage after pyelocaliceal surgery who does not respond to surgical urinary drainage may benefit from desmopressin.